2006
DOI: 10.2141/jpsa.43.330
|View full text |Cite
|
Sign up to set email alerts
|

Phytase Supplementation of Wheat-Based Broiler Diets Reduces Dependence on Meat-and-Bone Meal

Abstract: It is permissible to include meat-and-bone meal (MBM) in broiler diets in many countries outside the European Union, including Australia, where MBM is usually advantaged by being a relatively inexpensive source of phosphorus and protein. However, some producers may prefer to reduce their dependence on MBM as this feed ingredient has several disadvantages and may be a barrier to exports of chicken-meat. Therefore, the purpose of this experiment was to investigate the extent to which phytase supplementation can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
2
9
0
3
Order By: Relevance
“…In another study, Chinajariyawong and Muangkeow (2011) reported no effect on carcass yield and relative weight of visceral organs of chicks fed EO of palm kernel meal. The lack of any significant effect of probiotic on carcass characteristics, organs and most meat quality was reported earlier (Attia et al, 2003;Selle et al, 2006;Attia et al, 2011). In a study by Ashom et al, (2014) statistical changes were observed only for the pancreas, whereas the liver, heart, proventriculus and spleen of broilers remained unchanged when fed Roselle seed meal diets.…”
Section: Discussionsupporting
confidence: 52%
“…In another study, Chinajariyawong and Muangkeow (2011) reported no effect on carcass yield and relative weight of visceral organs of chicks fed EO of palm kernel meal. The lack of any significant effect of probiotic on carcass characteristics, organs and most meat quality was reported earlier (Attia et al, 2003;Selle et al, 2006;Attia et al, 2011). In a study by Ashom et al, (2014) statistical changes were observed only for the pancreas, whereas the liver, heart, proventriculus and spleen of broilers remained unchanged when fed Roselle seed meal diets.…”
Section: Discussionsupporting
confidence: 52%
“…A significant improvement in apparent and true metabolizable energy content of sorghum grain was reported by Pourreza and Ebadi (2006). Selle et al (2006) reported that phytase supplementation (750FTU/kg diet) of a wheat based diet significantly increased AME by 0.27 MJ/kg on a dry matter basis. A significant improvement in AME value for the broiler diets as a result of phytase supplementation was reported by Cortes et al (2007) and Selle et al (2007).…”
Section: Factors Affecting Variable Protein Utilisation Responses To mentioning
confidence: 99%
“…The efficacy of microbial phytase in improving P availability in poultry is clearly established (Broz et al 1994). There is also evidence of improved energy utilization (Ravindran et al 1999;Selle et al 2006) of wheat-based diets when supplemented with phytase. Farrel et al (1993) reported small but significant increases in the AME of sorghum-soybean meal-based diets (2810 versus 2870 kcal kg…”
mentioning
confidence: 99%